Asbestos Exposure and Malignant Pleural Mesothelioma: A Systematic Review of Literature - Santos,Cátia (2022)
Abstract Background: The relationship between exposure to asbestos and malignant pleural mesothelioma (MPM) is already well established. Nevertheless, much remains to be known about exposure thereto and the incidence and mortality from MPM. Objective: This systematic review aims to map the relationship between asbestos and MPM by studying the exposure to asbestos and the incidence and mortality of MPM. Methods: A systematic review was conducted relating asbestos and MPM. Exposure to asbestos, incidence, and mortality by MPM was reviewed. PubMed, Web of Science, Cochrane Library, RCAAP, DART-Europe, and the reference lists of included studies were searched, from January 1, 1960, to December 31, 2020. Methodological quality was checked, the risk of bias analysis was performed, a level of evidence grade was assigned, and descriptive data analysis was performed. Results: 3,484 unique citations were identified, which included seventeen observational studies that met inclusion criteria with a total of 1,104 patients. Heterogeneity is present between the included studies which range from a case series of 16 retrospective studies and 1 prospective study. Studies were mostly conducted in Europe, particularly in Italy (6), and were published between 1969 and 2020. The mean age of patients is approximately 66 years with a latency period between the first exposure and diagnosis of approximately 42 years. 14 studies present data regarding the occupational context and chrysotile and crocidolite are the most studied types of fibre. The incidence of cases occurred between the interval 1966 and 2014 and in 9 studies the mortality rate was 100% of patients. Conclusion: There is high evidence to support the relationships between asbestos and MPM. However, the relatively scant information provided by the studies reinforces the need for well-conducted research and implementation of National Mesothelioma Surveillance Centres at a global level.